Manejo floral na mangueira 'Ubá' no norte do Estado do Espírito Santo - Olmo, Bernardo Torres (2018)
The mango is one of the crops that has presented enormous potential for expansion in Espírito Santo (ES). In addition, there is a great demand from the juice and pulp processing industries for 'Ubá' mango fruit. However, there are few technologies developed for its management. The objective of this study was to evaluate the response of the use of different concentrations of paclobutrazol combined with the emergence (or not) of the branches, in the vegetative characteristics, flowering, fruiting and quality of 'Ubá' mango fruits. The experiment was conducted during the agricultural crops of 2015/2016 and 2016/2017, in commercial farming, in the city of Colatina-ES, in the factorial arrangement (2 x 5) + 1, the first factor being the emergence (with or without) (DR) and the second, five concentrations of paclobutrazol (cPBZ). In the agricultural crop of 2015/2016, concentrations of 0; 0.5; 1.0; 1.5; 2.0 grams of active ingredient per linear meter of plant canopy (g.m-1 linear of cup). In the agricultural year of 2017, 60% of the previous year's concentrations (0; 0.3; 0.6; 0.9 and 1.2 g.m-1 linear of plant canopy) were used. The source of the active ingredient used was the Cultar® 250 SC. The experimental design was in randomized blocks, with four replications, one plant per portion. In each block was added a control that was not submitted to any of the described treatments. For the vegetative characteristics, the effects of treatments on length (CRV) and diameter of vegetative branches (DRV) were analyzed. The number of inflorecences per branch (NPR), panicle length (CP) and number of fruits per branch (NFR) were evaluated in flowering. Finally, the physical characteristics were evaluated: number of fruits per plant (NFP), fruit mass (MP), productivity (PROD), fruit length (CF), fruit diameter (DF), pulp yield RP), angle hue of fruit peel (HC), hue hue of the pulp (HP) and firmness fruits (Fz). Also, the chemical characteristics of the fruits, being: pH, soluble solids (SS), titratable acidity (TA), ratio soluble solidsand titratable acidity (SS / AT). In the two agricultural crops evaluated, significant differences were observed in the comparison between the factorial and the control, in the variables: NFR, MF, CF, DF, RP and SS / AT. For the interaction (DR x cPBZ) significant difference was observed for the variable, RP. For the other evaluations, the factors were studied in isolation. For the DR factor there were significant differences in the variables: CP, NFR, CF, RP, HC, Fz, pH, SS, AT and SS / AT. For the second factor (cPBZ), the following xiv variables were significant: CRV, DRV, PROD, MF, CF, RP, pH, AT and SS / AT. Therefore, it was observed that the use of plant regulators decreased the vegetative growth of the branches. The emergence of the branches stimulated the lateral buds, increased the NFR and homogenized the reproductive branches. Also, the emergence of the branches and the concentrations of PBZ altered the physical characteristics of the fruit.